PENGARUH SULTAN MALIK AS SHALIH TERHADAP KESULTANAN SAMUDERA PASAI (1297-1326 M) - Guritno, Galih (Estoria: Journal of Social Science and Humanities, 2022)
The Article discusses the early history of the development of islam in the islamic sultanate of samudera pasai and discusses the life of samudera pasai during the literature study. Samudera pasai was the first area visited by arab traders and from this region the spread throughout the archipelago. During the leadership of sultan malik as shalih Samudera Pasai played an important role in the advancement of the sultane Samudera Pasai. Based on domestic and foreign sources as will as pasai’s historiography, this paper attempts to describe the islamization process of samudera pasai. Based on the narrative of ibn Battuta, a maroccon travel who visited pasai, it can be seen that some aspects of islam that have been implemented  have become an inseparable part of life, in this muslim kingdom.  Keywords: Samudera Pasai, Islam, Sultan Malik As Shalih